Structure of accounts - Harper, Karl.; Institute of Financial Services (Great Britain). School of Finance (Canterbury, Kent, U.K. : Chartered Institute of Bankers, 2004)
Incorporates all developments in accountancy practice, addresses how to assess the financial information contained in accounting documents and how to learn to base decisions on them. Especially helpful for non-accountants who have to work with accounts, and a recommended textbook for students of financial services.
Includes index.
oif 27/03/15
Loan
Keywords: Accounting